Longline and mesocosm cultivation of serrated wrack Fucus serratus (Phaeophyceae) - Eoghan Mánus Cunningham; Louise Kregting; Rebecca E. McKinney; Riddhi Salotra; Christine A. Maggs; Emma Healey; Jaimie T.A. Dick; Pamela J. Walsh (Applied Phycology)
Seaweed aquaculture is becoming increasingly important as the global seaweed market is set to exceed £20 billion by 2030, leaving natural populations at risk of overexploitation. Fucoids, such as Fucus serratus, are intertidal seaweeds hand-harvested for their use in agricultural, pharmaceutical, and biomedical industries. Despite many aspects of the biology of fucoids being well researched, there have been very few studies on their aquaculture. In this study, we grew F. serratus biomass from gamete life stages in the Queen’s University Marine Laboratory for 8 months and monitored their growth, amino acid and phenolic contents in a subtidal field trial. Gametes of F. serratus were successfully fertilized in vitro and attached to substrata: Tiles (mesocosm) and Dyneema Twine (subtidal). The growth of F. serratus on each substrate was monitored for 6 months in the laboratory facility with juveniles reaching 2–4 mm in length. The juveniles on twine were then deployed at the Strangford Lough test site and growth was compared against the juveniles on tiles after an additional two months. Prior to field deployment, individuals grown on tiles were significantly longer (~17%) than those on twine growing to ~3 cm, however, after the two-month deployment, the twine thalli grew significantly longer than those on the tiles (~33%) reaching ~6 cm in length. Subtidal F. serratus grown on twine had significantly higher amino acid content, whereas the phenolic content was significantly lower (~62 mg PGE g−1) than seaweed grown on the tiles (~128 mgPGE g−1). Growing F. serratus successfully in subtidal areas is highly important for providing sustainably sourced biomass to reduce reliance on wild harvesting. Further, cultivating in the subtidal zone will help to avoid competition for space from other aquaculture industries operating in the intertidal zone.